PENGARUH REBUSAN GAMBAS (Luffa cilindrica) TERHADAP KADAR GLUKOSA DARAH DAN PROFIL LIPID PADA TIKUS WISTAR DIABETES - Barinta Widaryanti; Arshita Eka Kurniawati; Nuriansyah Putri (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2016)
ABSTRACT Diabetets mellitus is a common desease which is caused by insulin secretion and action disorder. Prevelence of the desease was predicted to be increase 2,5 times in 2030, therefore, special treatment were needed to improve the quality of life diabetic patient. Recently, many natural drug has been developed for diabetic therapy. The objective of this research was to investigate the effect of boiled sponge gourd in reducing blood glucose dan lipid profile on male diabetic rats alloxan induced. Eighteen diabetic male wistar rats were divided into three groups, first grup were normal rats, second gorup were diabetic rats,and third gorup were diabetic rats that were treated with boiled sponge gourd for fourtheen days. The research showed that boiled sponge gourd was able to reduce blood glucose, total cholesterol and triglyceride. Keywords : Diabetes mellitus, gambas, anti diabetic drug, alloxan